Mechanical properties of compatibilized nylon 6/polypropylene blends; studies of the interfacial behavior through an emulsion model. Issue 18 (21st April 2014) - Huber, Tim; Misra, Manjusri; Mohanty, Amar K.
ABSTRACT The high interfacial tension between two immiscible phases in a polymer blend often prevents a homogenous stress distribution. Therefore, blends of Nylon 6 (Ny6) and polypropylene (PP) were compatibilized using two commercially available types of PP grafted with maleic anhydride (MAPP) with a low (∼2 %) and a high (∼7%) grade of maleation. The interfacial tension of compatibilized and non‐compatibilized blends of PA6/PP was calculated from the recoded data of oscillatory rheological measurements using an emulsion model. Both compatibilizers showed similar improvements in tensile strength of up to 25%, but the one low maleation grade compatibilizer showed improved impact properties (>200%). It could be shown that, despite, being more effective in reducing the interfacial tension, using a high grade of maleation in the compatibilizer causes no additional improvement in tensile strength over a low grade of maleation and even has a negative effect on the PA6/PP blend impact strength. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40792.